BIMBINGAN PENGEMBAGAN WAWASAN KARIR BAGI PESERTA DIDIK SD NEGERI WOLI BANG - Inggrit E. Bayang; Margerita A. Mapada, Salmon Wenigati, Yessy Mata, Petrus Mau Tellu Dony (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to examine career development guidance at Woli Bang Elementary Sch lhool, particularly in fourth grade. Another objective of this study is to identify career development challenges at Woli Bang Elementary School. The subjects of this study were the entire fourth grade class, consisting of twelve students: five boys and seven girls. From these results, we can conclude that not all fourth-grade students are focused on the learning process, making it difficult for them to identify and develop career paths within themselves.